Privatisasi Sistem Pelayanan Kesehatan Dan Implikasinya Bagi Perumusan Agenda Penelitian Dan Kebijakan Publik - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
In the face of the increasing potential of negativefirst generation impacts of medical industrialization and the privatization of health services in an era of globalization (i.e., increased incidence of infectious deseases and malnutrition among the poorest poor of I ndonesian population), the author of this article proposes the imperative offending a middle-way policy solution to integrate the public and private systems of health services to guarantee the provision of high quality services and the availability of accessible health services for the poor. After presenting a short discmcsion of the weaknesses of the public health system, he discusses the issue of medical industrialization and the privatization of health service institutions, and ends up with the presentation of five possible alternative of health service systems at the PUSKESMAS level.